Effectiveness of Structured Teaching Programmes in Enhancing Infection Control Practices Among NICU Nurses: A Systematic Review (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Infection control in Neonatal Intensive Care Units (NICUs) is crucial for reducing neonatal morbidity and mortality. Nurses play a key role in preventing infections, and structured teaching programmes (STPs) are increasingly used to enhance their knowledge and practices.Objective: This systematic review examines the effectiveness of STPs in improving infection control measures among NICU nurses.Methods: A comprehensive literature search was conducted in databases including PubMed, CINAHL, Scopus, and Cochrane Library. Studies evaluating STP outcomes in NICUs were included. The effectiveness of STPs was assessed based on improvements in nurses’ knowledge, attitudes, practices (KAP), and infection reduction rates.Results: Evidence suggests that STPs significantly improve nurses’ compliance with infection control protocols, including hand hygiene, personal protective equipment (PPE) use, and aseptic procedures. Interactive learning methods, such as simulations and workshops, yield better results compared to traditional lectures. Hospitals implementing STPs reported reduced rates of hospital-acquired infections (HAIs). However, challenges such as time constraints, resource limitations, and staff resistance hinder implementation.Conclusion: STPs are effective in enhancing infection control knowledge and practices among NICU nurses, contributing to improved patient safety. Healthcare institutions should integrate structured training into routine infection prevention programs. Further research is needed to standardize training models and evaluate long-term impacts.